A dual-factor model perspective on depressed inpatients: examining the dynamics of mental health and therapy outcomes - Brailovskaia, Julia; von Brachel, Ruth; van Hall, Franziska; Teismann, Tobias; Hirschfeld, Gerrit; Margraf, Jürgen (Frontiers in Psychiatry, 2024)
TBackground: The dual-factor model of mental health posits that mental health and mental illness constitute two distinct axes; accordingly the model identifies four mental health groups: (1) complete mental health, (2) troubled, (3) vulnerable, (4) symptomatic but content. Yet, only a few studies investigated effectiveness of therapy on both dimensions of mental health simultaneously. Against this background, the present study aimed to determine proportions and changes of group assignments in depressed inpatients undergoing therapy. Method: N=1044 depressed inpatients (age in years: M=53.36, SD=9.81, range: 17–83) completed a pre- and a posttreatment survey including questionnaires on depression, anxiety, and positive mental health. A total of n=328 persons completed the survey also at 6-month and12-month follow-up assessments. Results: In the classification that included depression symptoms and positive mental health, 49% of the participants were classified as troubled and 13.2% were classified as completely mentally healthy at the pre-treatment assessment. At the post-treatment, 9.5% were classified as troubled and 55.7% were classified as completely mentally healthy. In the classification that included anxiety symptoms and positive mental health, 21.9% of the participants were classified as troubled and 14.2% were classified as completely mentally healthy at the pre-treatment assessment. At the post-treatment, 3.7% were classified as troubled and 56.1% were classified as completely mentally healthy. About 10 to 20% of patients showed an improvement in depression/anxiety and positive mental health, whereas another 10 to 20% showed a reduction in depression/anxiety, but only a minor increase in positive mental health between pre- and post-treatment. Conclusion: Findings are in line with past research inspired by the dual-factor model in showing that enhancing positive mental health and alleviating psychopathology do not always co-occur in treatment. It is therefore important to implement measures of both psychopathology and positive mental health in therapy outcome studies, and to promote interventions targeting both psychopathology and positive mental health.